PROPOSAL FOR AN ASSESSMENT ACTIVITY IN GEOGRAPHY USING KEY THEMES FROM THE GLOBAL AND NATIONAL CONTEXT - Aires, Marina; de Mendonça, Arthur Galvão (Seven Editora, 2026)
This experience report refers to an assessment activity proposed for the 8th grade of lower secondary education, involving students from the Augusto Pugnaloni Municipal School, located in the municipality of Petrópolis (Metropolitan Region of Rio de Janeiro – RMRJ). The activity was entitled “Simulating a United Nations Conference.” To achieve the objectives of the activity, active methodology proposals were developed using the classroom space, allowing students to discuss the proposed themes, conduct research on them, create posters, and present them to their classmates. At the end of the activity, a debate was held on the importance and learning outcomes of each topic discussed. DOI: https://doi.org/10.56238/sevened2026.008-030